Serum adropin and nitric oxide levels in missed abortus cases - Paşaoğlu, Hacer; Deniz, Rulin (Journal of Surgery and Medicine, 2021)
Background/Aim: Missed abortus is an emergency obstetric pathology, defined as intrauterine fetal viability loss before the 20th week of pregnancy. It is known that there is a correlation between endothelium dysfunction, neovascularization, hemodynamic regulation and adropin and nitric oxide levels. In this study, it is intended to research the possible roles of adropin and nitric levels in etiopathogenesis. Methods: In this case-control study, a total of fifty-nine volunteers, including healthy pregnant women and missed abortion cases, were included in the study. They were divided into 2 groups, as healthy individuals (Group 1, n=29), and those diagnosed with missed abortus (Group 2, n=30). Group 2 patients were followed weekly until β-HCG values fell below 5 ng/ml after termination. Serum adropin and nitric oxide levels were measured in all participants and those diagnosed with missed abortion when negative β-HCG value was obtained after termination. Results: Serum adropin and nitric oxide levels were significantly low in the missed abortus group (P=0.03) compared to healthy pregnant women, and in the missed abortus group compared to those whose β-HCG fell below 5 ng/ml after termination (P=0.02), while nitric oxide levels were similar in the latter comparison (P=0.38). Regarding age, body mass index, obstetric parameters, and other biochemical parameters, the two groups were similar (P>0.05 for each). Conclusion: This is the first research which evaluates adropin levels in missed abortus cases. Lower adropin and nitric oxide levels in missed abortus cases, and their increase after post-termination show that they may be playing a role in abortus etiopathogenesis.